Script for describing the San Francisco Monumental Complex for foreign tourists and its spread out among tourist guides - Duchi Cujilema, María Patricia (2008)
After, making inquieres, and interviewing Tourists, about their Knowledge of the San Francisco Square, the conclusion has been, that, there is not enough information, especially for foreign tourist and guide tourist. In addition to it, I have visited to the authorities of San Francisco Monumental Complex, there is not a complete information for tourists, tourist Guides, and students, about this theme in English, so that its authorities have asked me to make a script of this important cultural, historic, and patrimony Complex from Quito Ecuador. The script content has a physical and architectonic description, location, legends, history of every single building of the San Francisco Monumental Complex. The information has been taken directly of the oldest manuscripts that are in the file of Pedro Gocial Museum, also Municipio de Quito, and Catholic University Library. In this research, the most outstanding paintings that belong to the XVI century, of San Francisco Monumental Complex have been placed. Finally, I wrote down a script that is my proposal, which has a physical description, historical, architectonical, of square, atrium, chapel, convent and Museum of San Francisco Monumental Complex. In order to give a clear information about this wonderful Tourist Complex from Quito. Further, I have added a basic glossary with architectonical terms that have been used in the script, in order to help the users, to understand its technical words.